IMMUNOHISTOCHEMICAL ANALYSIS OF BREAST CANCER SUBTYPES AND THEIR CORRELATION WITH Ki 67 INDEX - Naeem, Shagufta; Naz, Shabana; Riyaz, Anila; Jehangir, Fouzia; Afzal, Naeema (Journal of Ayub Medical College Abbottabad, 2018)
Background: Breast cancer is the second most common cancer in females including Pakistan. Nowadays immunohistochemistry has revolutionized management of breast cancer. In this study, we determined the frequency of various subtypes of breast cancer on the basis of immunohistochemical staining and their correlation with ki 67 index. Methods: Fifty consecutive diagnosed breast cancers cases received during the period February 2014 to February 2016, at Ayub Medical College, Pathology Department were included in this cross-sectional study. Immunohistochemistry for Estrogen receptor (ER), Progesterone receptor (PgR), Her2neu and ki 67 index were applied and the results were recorded. Results: Out of 50 cases, 34 (68%) were positive for ER and PgR, 6 (12%) were positive for Her 2neu while 6 (12%) were triple positive and 4 (8%) were triple negative. Conclusion: Low risk Luminal A was the most frequently encountered breast cancer category. Keywords: ER, PgR, Her 2 neu; Triple positive breast cancer; Triple negative breast cancer